Industrial psychology - McCormick, Ernest J.; Tiffin, Joseph (London : George Allen &Unwin Ltd., 1974)
The field of industrial psychology addresses itself to the wide spectrum of human problems that arise in the production, distribution, and consumption of the goods and services of the economy.
Part I. Introduction -- Part II. Personnel selection and evaluation -- Part III. The Organizational and social context of human work -- Part IV. The Job and work situation -- Part V. Accidents and human errors -- Part VI. Psychological aspects of consumer behavior -- Index
Includes index.